Projecting Nation South African Cinemas After 1994. - Moyer-Duncan, Cara (Michigan State University Press, 2020)
"Projecting Nation explores the ways in which national and transnational forces have shaped the representation of race and nation in South African films produced after the transition to a multiracial democracy"-- Provided by publisher.
Description based upon print version of record.
Keywords: National Film and Video Foundation (South Africa); Post-apartheid era -- South Africa.; Post-apartheid era in mass media.; Motion picture audiences -- South Africa.; Motion pictures -- South Africa.; Motion picture industry -- South Africa -- History.; Ère post-apartheid -- Afrique du Sud.; Ère post-apartheid dans les médias.; Cinéma -- Publics -- Afrique du Sud.; Cinéma -- Industrie -- Afrique du Sud -- Histoire.; Cinéma -- Afrique du Sud.; PERFORMING ARTS / General; Motion picture audiences; Motion picture industry; Motion pictures; Post-apartheid era; Post-apartheid era in mass media; South Africa; History